PENGARUH REALISASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) TERHADAPPERTUMBUHAN EKONOMI DI PROVINSI SUMATERA BARAT - Susila, Indra; Yolamalinda, Yolamalinda; Hidayat, Rian (Pendidikan Ekonomi, 2014)
ABSTRACT This study aims to demonstrate and analyze how far the effect Goverment expenditure and Investment of the Economic Growth in West Sumatra province . This study used a sample of 15 fifteen -year budget that comes from the realization and Investment from 1997 to 2011 . Kind of research conducted in this study using quantitative research using time series of 1997 to 2011.Tools of data analysis in this study uses an econometric approach to the multiple regression equation . From the analysis of the data showed that the variables Routine ( X1 ) partially no effect on Economic Growth in West Sumatra Province , Development Expenditure variables ( X2 ) and partially significant effect on economic growth in the province of West Sumatra , and the investment variable ( X3 ) partial had no effect on Economic Growth in West Sumatra province . Overall the studied variables have an influence on Economic Growth in West Sumatra province .